1999
DOI: 10.1002/(sici)1520-6505(1999)8:3<101::aid-evan5>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The social organizations of squirrel monkeys: Implications for ecological models of social evolution

Abstract: “Squirrel‐monkeys occur in a considerable number of slightly different forms, but all are built upon a similar body plan and have a basic color scheme. One of the larger races—from inner Perú—is also the most colorful and one of the brightest colored of all mammals. It may be taken as a point of departure. The top of the head and the upper and outer parts of the body and the upper side of the basal half of the tail are a vivid green, with a pepper and salt effect of yellow and gray. The face is pure white exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 62 publications
(10 reference statements)
5
73
0
1
Order By: Relevance
“…Mitchell et al, 1991;Borries, 1993;Barton et al, 1996;Sterck et al, 1997;Koenig et al, 1998;Boinski, 1999;Koenig, 2000;Steenbeek & van Schaik, 2001). The same observation is sometimes consistent with all three models.…”
Section: Three Basic Modelsmentioning
confidence: 67%
“…Mitchell et al, 1991;Borries, 1993;Barton et al, 1996;Sterck et al, 1997;Koenig et al, 1998;Boinski, 1999;Koenig, 2000;Steenbeek & van Schaik, 2001). The same observation is sometimes consistent with all three models.…”
Section: Three Basic Modelsmentioning
confidence: 67%
“…As a result, most squirrel monkey populations are under intense predation pressure (Fedigan et al, 1996). Predation risk has profoundly affected many aspects of squirrel monkey biology, including growth and development (Boinski, 1987;Boinski, 1999;Boinski et al, 2003). In a study of red squirrel monkey (Saimiri oerstedi) behavioral ecology in Costa Rica, Boinski (Boinski, 1987) found that infants experienced higher rates of predation than any other age class, with more than 50% of infants dying within the first six months of life.…”
Section: Introductionmentioning
confidence: 99%
“…By six months of age, when juveniles are only 40-50% of adult size, foraging activity and locomotor repertoires are generally indistinguishable from adults (Boinski, 1989;Boinski and Fragaszy, 1989). Moreover, once juvenile squirrel monkeys have become independent, they must travel an average of 2-4 km day -1 to remain with the group and gain access to distributed foraging resources, such as fruit and invertebrate prey (Terborgh, 1983;Mitchell, 1990;Boinski, 1999). In summary, squirrel monkeys are an excellent group in which to investigate how developmental changes in limb mechanics might impact locomotor performance in young mammals.…”
Section: Introductionmentioning
confidence: 99%
“…New World monkeys present an useful group for examining hypotheses of sexual dimorphism. Squirrel monkeys probably exhibit the most extensive geographic variation in social organization compared with other primates (Boinski and Cropp, 1999;Boinski, 1999). Radiation includes some well-defined monophyletic clades within which phylogeny can be controlled.…”
Section: Resultsmentioning
confidence: 99%